Studi Perladangan Berpindah Dari Suku Wemale Di Kecamatan Inamosol Kabupaten Seram Bagian Barat - Johan M Matinahoru (Faculty of Agriculture, Pattimura University, 2013)
Shifting cultivation is a farming system in which farmers cultivate through a movement of activity from a place to another in the secondary or primary forest. Wemale tribe in the Inamosol District of West Seram Regency are able to open forest area about 0.2 – 1.0 hectare in each year for practing the shifting cultivation. To understand how Wemale tribe practiced the shifting cultivation, a research has been conducted with the main objevtive to know the factors that determined the variation of the land size of the shifting cultivation. The method used in the research was by interview and direct observation in the field. The results of the research indicated that variation of land size of the shifting culvation that was practiced by the Wemale tribe were the number of household labors and the number of children in the household that were still active in the process of education